2019
DOI: 10.1029/2019je006082
|View full text |Cite
|
Sign up to set email alerts
|

MarsWRF Convective Vortex and Dust Devil Predictions for Gale Crater Over 3 Mars Years and Comparison With MSL‐REMS Observations

Abstract: Key Points MarsWRF output combined with thermodynamic theory is used to predict temporal and spatial trends of “dust devil activity” in Gale Crater Modeled activity and observed vortex pressure drops are both greatest in local summer, peaking ~13:00‐14:00, and smallest in winter Sensible heat flux drives increased activity as MSL climbs, but pressure drop numbers increase faster, unless a threshold activity is used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(102 citation statements)
references
References 61 publications
8
93
1
Order By: Relevance
“…They furthermore suggested that the frequency of cleaning events (once every few hundred sols) was consistent with encounters of vortices with pressure drops larger than some value in the range 6–40 Pa. Vicente‐Retortillo et al (2018) studied dust correction factors on the ultraviolet flux sensors on the Curiosity rover and found that at that site (Gale crater, 4.6°S, not far from InSight) dust removal by convective vortices and nighttime winds tended to occur around perihelion, until L s ~ 300°, while dust tended to accumulate until the end of the aphelion season ( L s ~ 180°). The vortex activity at Gale, and its dependence on the meteorological setting, has recently been documented by Newman et al (2019).…”
Section: Short‐term Solar Flux Variationsmentioning
confidence: 86%
“…They furthermore suggested that the frequency of cleaning events (once every few hundred sols) was consistent with encounters of vortices with pressure drops larger than some value in the range 6–40 Pa. Vicente‐Retortillo et al (2018) studied dust correction factors on the ultraviolet flux sensors on the Curiosity rover and found that at that site (Gale crater, 4.6°S, not far from InSight) dust removal by convective vortices and nighttime winds tended to occur around perihelion, until L s ~ 300°, while dust tended to accumulate until the end of the aphelion season ( L s ~ 180°). The vortex activity at Gale, and its dependence on the meteorological setting, has recently been documented by Newman et al (2019).…”
Section: Short‐term Solar Flux Variationsmentioning
confidence: 86%
“…In local summer, Newman et al. (2019) found that the vortex encounters detected by Curiosity exhibited a double‐peak structure at LTST 10:00–11:00 and 13:00–14:00 (see also simulations by Chapman et al., 2017). This double‐peak structure is not found during the first northern summer season experienced by InSight.…”
Section: Vortex Population and Statisticsmentioning
confidence: 97%
“…This causes the daytime wind direction (Figure a) to vary significantly, from −90° (wind blowing from the W) to +120° (wind blowing from the SE), and the mean wind speed to decrease significantly to reach a steady value of about 5 m/s until the decay of the dust storm between Sols 130 and 140 (Ls 8–13°). Convective activity is closely linked to both the wind stress at the surface and the surface‐to‐air temperature difference (e.g., Newman et al, ; Rennó et al, ). Thus, following the decrease of both ambient wind speed and daytime surface temperature, the number of pressure drops caused by convective vortices also decreases during this stage, ranging from 1 to 12 pressure drops per sol. From Sol 130 to Sol 220 (Ls 8–51°), a significant change appears again in the atmospheric activity: The mean wind direction rapidly switched from −40° to +130°, denoting a reversal of the wind direction from “NW to SE” to “SE to NW.” This change in Elysium Planitia was predicted by prelanding climate modeling (Spiga et al, ).…”
Section: Comparison With Insight Meteorological Measurements and Implmentioning
confidence: 99%